Ulusal Ve Yerel Düzeyde Yoksulluk Azaltma Stratejileri: İstanbul’da Sosyal Yardım Uygulamaları - Eryıldız, Fatma Gül (Fen Bilimleri Enstitüsü, 2016)
ÖZET Yoksulluğun mutlak bir tanımı olmamasına rağmen yoksulluğu algılama ve tanımlama tarzı, ona karşı tavrımızı belirlemektedir. Yoksulluk özetle eşitsizlik anlamına gelmektedir ama nasıl bir eşitsizlikten bahsettiğimizin yanıtı önemlidir. Gelir dağılımında eşitsizlik, kaynakların dağılımında eşitsizlik, hizmetlerin kalitesinde ve erişilebilirliğinde eşitsizlik, neticede bireyin kendini yeniden üretmesinde yaşanılan eşitsizliktir. Yoksulluk ölçümleri yapılırken önce gelir ve tüketim harcamalarına bakılsa dahi bugün bunun yeterli olmadığı, bazı sosyal ve siyasal gelişmişlik kriterlerinin de hesaplamaya katılması gerektiği görülmüştür. Yoksulluğun kısacası  eşitsizliğin etkilerini hafifletmek, toplumsal kriz oluşmasının önüne geçmek ve yönetilebilir kılmak için özellikle gelişmekte olan ülkelere uluslararası kuruluşlarında yönlendirmesiyle devletlerin uyguladığı yöntem isesosyal politikadır. Sosyal politikanın yöntemsel olarak uygulanması sosyal koruma araçlarıyla olmaktadır. Sosyal sigorta, sosyal hizmetler ve sosyal yardımlar sosyal korumanın bileşenleridir. Yoksulluğu azaltma aracı olarak sosyal yardımlar bu bileşenlerin içinde son başvurulan, diğer bileşenlerin çözemediği sorunlarda destek alınması gereken bir araçtır. Günümüzde merkezi yönetimden yerel yönetime inen bir hiyerarşide sosyal yardımlara verilen önemin arttığı ve can simidi işlevi gördüğünü düşünülmektedir. Bu sebeple tez kapsamında, 2000’li yıllardan sonra uluslararası kuruluşların gelişmekte olan ülkelere bilgi üretimi ve yönlendirme anlamında en önemli kuruluşlardan biri olan Dünya Bankası’nın sosyal yardımlara dair uygulama ve söylemelerinden başlanarak,  ulusal düzeyde ve yerel yönetimlerin sosyal yardım anlayışı incelenmiştir. Yapılan incelemede söylem bazlı Dünya Bankası’nın çizdiği çerçeve ile merkezi yönetimin çizdiği çerçeve arasında fark bulunmamaktadır. Çalışmanın kuramsal arka planında yoksulluk, yoksulluğa değişen yaklaşımlar, yoksulluk ölçüm yöntemleri, büyüme ve gelir dağılımı arasındaki ilişkiye bakılmıştır. Kuramsal arka planının ardından bu tez kapsamında incelenen sosyal devlet, sosyal politika, sosyal koruma ve sosyal yardım kavramlarına yaklaşım netleştirilmeye çalışılmış bununla beraber Dünya Bankası’nın yoksulluğu azaltma araçları üretmede, yönlendirmede ve uygulamada nasıl bir yaklaşım içinde olduğu, özellikle gelişmekte olan ülkelerin karar alıcıları içinde nasıl bir konuma sahip olduğu belirtilmiştir. Sosyal yardım uygulama sürecinde hiyerarşik olarak üstten alta inecek şekilde tüm aktörlerin konumları ve rolleri ortaya konulmuştur. Çalışmanın saha kısmında merkezi yönetimin sosyal politika uygulamaları ve merkezi yönetimin kararlarının yerel yönetimleri nasıl etkilediğine değinilerek İstanbul Bölgesi’nde yerel yönetimlerin değişen sosyal yardım uygulamaları incelenmiştir. İstanbul Büyükşehir Beldiyesi’nin uygulamalarından başlanmış daha sonra, merkezde yer alan iktidar ve muhalefet parti yönetiminde iki belediye (Beyoğlu ve Şişli Belediyesi) ve çeperde yer alan iktidar ve muhalefet parti yönetiminde (Beylikdüzü ve Bağcılar Belediyesi) alınan istatistiki veriler ve derinlemesine uzman görüşmeleri kullanılmıştır. Merkezi yönetim faydalanıcıları belirlerken her ne kadar ilk aşamada nesnel yöntemleri kullansalarda nihai karar mütevelli heyetine bırakılmaktadır.Yerel yönetimler ise nesnel hiçbir yöntem kullanmamakla beraber yararlanıcıları belirlerken merkezi yönetimle biçim olarak aynı süreçlere sahiptir. Erişilen bilgiler ve yapılan hesaplamalarda belediyelerin yaptıkları sosyal yardım faaliyetlerin sadece nüfusun en muhtaç kesimini karşılayacak şekilde yapıldığı görülmüştür.

In this study that is starting from the social assistance policies developed in the national scale and reaching to the local scale, the role of the social assistances as a social policy instrument within the poverty reduction strategies was examined through the case study of Istanbul. The sample of Istanbul was analyzed by way of the implications of central and local administrations. In this framework, which actors have taken a part and what kind of roles they have had sought in the manner of showing the hierarchy from the internatonal level to the national and local levels. How the neoliberal policies after 2000 and the changing approaches of international institutions to the concept of social policy have affected the national and local scale policy making processes was examined. Hereby, the increasing importance of developing an appropriate social policy in an atmosphere that income inequality is continously increasing was argued. For this aim, by providing some samples from certain municipalities of Istanbul, the social policy development methods and implications were examined in the urban scale. How the social assistances as an instrument have contributed to the poverty reduction was investigated. The necessity of tackling poverty multidimensionally and whether the approach of giving the main role to the social assistances in the poverty reduction strategies has been effective or not was revealed.  Within the scope of this study, the concepts of poverty, social policy, social protection and social assistance were elaborated conceptually. The relationship between the World Bank Reports and the Development Plans was revealed and the changing implications of central and local administrations were examined. The social policies determined by the World Bank for the developing countries, especially Turkey, were semtinized and the effects of this on the applications in Turkey was revealed. The qualification and function of the social policies in Turkey after 2000 was mentioned. In the theoretical background of the study, poverty, different approaches to the poverty, methods of poverty measurement, the relationship between growth and income distribution were searched. Subsequent to the theoretical background, the approach to the concepts of social policy, social protection and social assistance was clarified. In addition, what kind of an approach the World Bank has used in the production, direction and implication processes of the poverty reduction instruments and; what kind of an influence the World Bank has had in the decision-making processes of the developing countries were indicated. In the social assistance implication process, the roles and influences of all actors from top to bottom were revealed. Although there is not any certain definition of poverty, the way of perception and definition of poverty shows our attitude against it. Poverty does not mean inequality in brief but the answer of what kind of an inequality we are talking about is important in this point. In equality in the income distribution, inequality in the resource allocation, inquality in the quality and accessibility of services and eventually inequality in the reproduction of individuals. Even if the income and consumption expenditures are surveyed in the first instance, it is seen that this is not enough today and some social and political development criterions also must be considered at the same time. The method which is used for diminishing the effetcs of poverty or inequality in brief, preventing and controlling the social crisis and; which is applied by the states through the guidance of the international instituons is the social policy. The measurement of the poverty is important in order to develop social policy but measuring poverty by using one-way or only quantitative measurements has been inadequate. Class differences must be analyzed in detail; heterogenious structure of the poor (the poverty of woman, child, old, migrant etc) must be taken into consideration and; spatial and social disintegration must be revealed and; more clearly the view of the poverty in the social life must be drawn transparently.  Istanbul, when we look to the ratio of poverty, is not a region that has the biggest poverty but because of the population density it is accepted as a region having the biggest poverty. Because of this, examining the case of Istanbul matters. Generally, the view seeing poverty as a problem that cannot be destroyed but decreased is common. It is seen that poverty keep up –to-date as an important problem and it is not possible to sort poverty and income distribution out through economic growth. The view accepting that decreasing the poverty in the shortest term is only possible through the straight-forward approach instruments, the production of appropriate social policies is common in international and national levels. In the years when the concept of social policy first emerged, it was used for making the life of workers better (compulsorily) but today evolved into a different objectivity. Social policy still involves workers’ rights but the policies produced towards especially disdavantaged groups predominate. The procedural implementation of the social policy has been via social protection (security) instruments. Social insurance, social services and social asssistance are the components of the social protection. Indeed, social asssistance as an instrument of the poverty reduction are less frequently used instrument among these elements that involved in the problems which other elements could not overcome. At the present time it is thought that the importance given to the social asssistance have increased in a hierarchy from the centre to the local and worked as a flotation ring. It is thought that social exclusion and division decrease in a society which has appropriate social policies. When we examined the public social protection expenses since 2006, it is seen that Turkey ranges below OECD countries. Although Turkey is 17th in G-20, social protection expenses remains quite low. Full employment target is important in terms of social policy. Although it is seen that social assistances work for decresing poverty, it has been weak and inadequate in terms of targeting the poorest in the society and missing the complementary effects of other social protection elements. On the other hand, although we see that only a small proportion is left for the social assistances, it is important to emphasize that the amount of the assistance has been accelerated per year. Besides, for distributing the social assistances to the poor in the highest rate, it is necessary to determine the poverty profile of the poor correctly and to apply different programmes towards different poor groups. For this reason, within the scope of the thesis, the social benefit understanding of the local governments in Turkey after the 2000s will be examined by starting from the implications and discourses of the Wold Bank as one the most important international organisations in the information production and policy-direction for the developing countries.   The World Bank is one of the institutions producing policies in the international system and world economy. The World Bank determines the content of the concepts and sets the agenda. It is seen that the World Bank is not only an economic institution but also a political, ideological and cultural formation. Together with giving loans to the developing countries, the World Bank also makes the information production. The main attempts of the World Bank about the poverty reduction are mitigating the social risk, governing, preventing and decreasing. On the one hand the World Bank predicts a market-driven economic growth; on the other hand it makes an emphasize on the enhancement of the social capital. It emphasizes creating opportunities for the poor,  strengthening them and increasing the security of them. When we look to the social assistance policies of the central government, there are first the Ministry of Family and Social Policy (MFSP) and under its administration General Directorate of Social Assistance and Solidarity (GDSA) and Foundation of Social Help and Solidarity (FSHS). The discourse arguing that one of the advantages of organisation of the FSHS as a foundation is its conformity to the principle of governance took place in the World Bank reports firstly and then the target aiming at the cooperation between central and locak administrations and NGOs writing in the Development plans shows that these plans started to be implemented. In addition, although the income of the FSHS is generated mostly from the public funds, it was also received supoort from benefactors. By establishing a foundations-network organised in the country level, the FSHS gives support with the social assistance programmes. Even though the interventions in the economic realm have been made by the state, the FSHS, which is acting as an NGO via charity activities, has provided the political continuity of the central government with the localities at the same time. The share of the MFSP taken from the general budget has increased each year and in 2014 it reached to 3,97 %. Even in the current situation, for a ministry producing social assistance and service, a low amount has been budgeted. The GDSA contained within the MFSP has had 60% more budget than the MFSP and this is an important data for understanding the increasing importance of the social assistances.  The World Bank emphasizes that health and especially education is important for increasing the social capital and the World Bank policies have evolved into the increase in the social capital rather than the assistance to the disadvantaged groups. The World Bank opened a credit to the Social Risk Mitigating Project for decreasing the effects of the 2001 crisis. The conditional cash transfer has constituted the biggest part of this project. The still ongoing conditional cash transfer implementation has been realised not via the World Bank loans but the budget of FSHS. Within this scope, conditional cash transfer programme is in the field of education and health, although the share of the education is higher.   When we look to the statictics of the institutions distributing social assistances in the national level, as we mentioned before, the main institution is the MFSP and the total ratio of the local governments is 3,9 %. Although this ratio shows that the role of the local governments in the social assistances, the increasing rate of the municipalities among the institutions providing social assistance also shows the will for increasing the responsibilities of the localities in the social assistance provision.  In the fieldwork of the study, the changing social assistance implementations of the local governments in Istanbul were examined by referring to how the central administration has affected the social policy implementations and the local governments. For this, statistical data collected from two municipalities in the center (Beyoğlu ve Şişli Municipalities) and two municipalities in the periphery (Beylikdüzü ve Bağcılar Municipalities) and in-depth interviews with the authorities were used. When we look to the social assistance provided by the local governments, it is noticed that the assistances were concentrated on the public relief rather than the financial aid. The information exchange between the local governments themselves or with the central administration is quite limited.  Although the central administration has used the objective methods firstly in the determination of the beneficiaries, the last decision was taken by the boards of trustees. On the other hand, local governments have not used any objective method but had the same processes with the central administration in the determination of the beneficiaries. According to the reached information and calculations, it is seen that the social assistance facilities of the municipalities involves only the most needy part of the population. While it is noticed that the AKP municipalities are more experienced than the CHP municipalities in terms of the social assistance (they started the social assistance earlier; they have more experienced data set and; they are more quantitatively), the CHP municipalities have concentrated on social services and socio-cultural activities more but started to increase and develop the social assistance implications by feeling the pressure of the increasing importance of the social assistance. I
Poverty Reduction strategies On National And Local Level: Social Assistance Implementation On Istanbul
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: yoksulluk; sosyal yardım; yerel yönetimler; poverty; social assistance; local autority